Photosynthetic Light Harvesting and Thylakoid Organization in a CRISPR/Cas9 Arabidopsis Thaliana LHCB1 Knockout Mutant - Sattari Vayghan, Hamed; Nawrocki, Wojciech J.; Schiphorst, Christo; Tolleter, Dimitri; Hu, Chen; Douet, Véronique; Glauser, Gaëtan; Finazzi, Giovanni; Croce, Roberta; Wientjes, Emilie; Longoni, Fiamma (Frontiers in Plant Science, 2022)
Light absorbed by chlorophylls of photosystem II and I drives oxygenic photosynthesis. Light-harvesting complexes increase the absorption cross-section of these photosystems. Furthermore, these complexes play a central role in photoprotection by dissipating the excess of absorbed light energy in an inducible and regulated fashion. In higher plants, the main light-harvesting complex is trimeric LHCII. In this work, we used CRISPR/Cas9 to knockout the five genes encoding LHCB1, which is the major component of LHCII. In absence of LHCB1 the accumulation of the other LHCII isoforms was only slightly increased, thereby resulting in chlorophyll loss leading to a pale green phenotype and growth delay. The photosystem II absorption cross-section was smaller while the photosystem I absorption cross-section was unaffected. This altered the chlorophyll repartition between the two photosystems, favoring photosystem I excitation. The equilibrium of the photosynthetic electron transport was partially maintained by a lower photosystem I over photosystem II reaction centre ratio and by the dephosphorylation of LHCII and photosystem II. Loss of LHCB1 altered the thylakoid structure, with less membrane layers per grana stack and reduced grana width. Stable LHCB1 knock out lines allow characterizing the role of this protein in light harvesting and acclimation and pave the way for future in vivo mutational analyses of LHCII.